Dense Pt Nanowire Electrocatalyst for Improved Fuel Cell Performance Using a Graphitic Carbon Nitride‐Decorated Hierarchical Nanocarbon Support. Issue 30 (17th June 2021) - Fang, Baizeng; Daniel, Lius; Bonakdarpour, Arman; Govindarajan, Ruben; Sharman, Jonathan; Wilkinson, David P.
Abstract: An innovative strategy is presented to engineer supported‐Pt nanowire (NW) electrocatalysts with a high Pt content for the cathode of hydrogen fuel cells. This involves deposition of graphitic carbon nitride (g‐CN) onto 3D multimodal porous carbon (MPC) (denoted as g‐CN@MPC) and using the g‐CN@MPC as an electrocatalyst support. The protective coating of g‐CN on the MPC provides good stability for the electrocatalyst support against electrochemical oxidation, and also enhances oxygen adsorption and provides additional active sites for the oxygen reduction reaction. Compared with commercial carbon black Vulcan XC‐72R (denoted as VC) support material, the larger hydrophobic surface area of the g‐CN@MPC enables the supported high‐content Pt NWs to disperse uniformly on the support. In addition, the unique 3D interconnected pore networks facilitate improved mass transport within the g‐CN@MPC support material. As a result, the g‐CN@MPC‐supported high‐content Pt catalysts show improved performance with respect to their counterparts, namely, MPC, VC, and g‐CN@VC‐supported Pt NW catalysts and the conventional Pt nanoparticle (NP) catalyst (i.e., Pt(20 wt%)NPs/VC (Johnson Matthey)) used as the benchmark. More importantly, the g‐CN‐tailored high‐content Pt NW (≈ 60 wt%) electrocatalyst demonstrates high PEM fuel cell power/performance at a very low cathode catalyst loading (≈ 0.1 mgPt  cm −2 ). Abstract : Herein, an innovative interfacial engineering strategy, through which a hierarchical multimodal porous carbon catalyst support is coated with a thin graphitic carbon nitride layer to enhance the stability and improve electrocatalytic activity toward the oxygen reduction reaction, is reported. The engineered support with dense Pt nanowire electrocatalyst demonstrates improved fuel cell polarization performance and electrochemical stability.